Electrical engineering : - Christie, Clarence Victor (McGraw-Hill, 1952)
The more important additions include sections on complex alternating waves and wave analysis, on polyphase alternating current circuits, on the construction of the characteristic curves of direct-current generators and motors, on the design of directand alternating-current machinery, on theB londel diagram for the synchronous motor, on the symbolic method of analysis of the induction motor, on alternating-current commutator motors, and finally a chapter on electrical measuring instruments.